2007
DOI: 10.1002/jat.1253
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium accumulation and binding characteristics in intact Sertoli/germ cell units, and associated effects on stage‐specific functions in vitro: insights from a shark testis model

Abstract: The increased human use of cadmium (Cd) and its increased occurrence in the environment is of concern. The testis is sensitive to Cd because of the steroid-mediated regulation of spermatogenesis, high levels of DNA synthesis and gene transcription, all of which varies in a stage-related manner. Validated techniques (acridine orange vital staining to detect apoptosis and dextran-rhodamine exclusion to assess blood-testis barrier function) were recently developed and the shark testis was proposed as an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Using a 109 objective, 6-10 fields of view of each triplicate AO-and PI-stained well of dispersed spermatocysts (*50 cysts per field of view), were randomly captured and stored on computer for later analysis. A cyst was designated AO-positive if it contained three or more bright green punctate fluorescent spots, a standard previously used [14][15][16]. A cyst was designated PI-positive if at least half of the cyst in the plane of focus was filled with bright red round fluorescent nuclei.…”
Section: Ao and Pi Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a 109 objective, 6-10 fields of view of each triplicate AO-and PI-stained well of dispersed spermatocysts (*50 cysts per field of view), were randomly captured and stored on computer for later analysis. A cyst was designated AO-positive if it contained three or more bright green punctate fluorescent spots, a standard previously used [14][15][16]. A cyst was designated PI-positive if at least half of the cyst in the plane of focus was filled with bright red round fluorescent nuclei.…”
Section: Ao and Pi Stainingmentioning
confidence: 99%
“…A curious finding though in both studies was thus the relative resistance of immature premeiotic stages (PrM, stem cell and early-stage spermatogonia) to apoptosis in the normal testis and after spermatoxicant exposure in vivo. However, this was not maintained in vitro as the immature spermatogonial clones spontaneously entered apoptosis during 2 days culture [16].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In toxicological studies, S. acanthias testis preparations in vitro were used to study cadmium effects on spermatogenesis (McClusky, 2008 a ). Cadmium accumulated in spermatocysts in culture, and experiments indicated that the binding was specific.…”
Section: Application Of Primary Culture Technologymentioning
confidence: 99%
“…Cadmium accumulated in spermatocysts in culture, and experiments indicated that the binding was specific. Micromolar concentrations of cadmium caused apoptosis over 2–4 days in culture, and evidence indicated that the elements of the blood‐testis barrier function were negatively influenced (McClusky, 2008 a ). Foetal bovine serum produced both apoptosis and thymidine incorporation in spermatocyst cultures, and the apoptotic effect was decreased by addition of androgen (McClusky, 2008 b ).…”
Section: Application Of Primary Culture Technologymentioning
confidence: 99%